Implementation of the Learning Digitalization Policy in Improving the 21st Century Skills of Elementary School Students - Pian Firman Hidayat; Imam Syuhada; Dadan Dahtiar; Waska Warta (Civiliza Publishing, Indonesia., 2025)
This study aims to analyze the implementation of the learning digitalization policy in improving 21st century skills at SDN 1 Sukamanah. Along with the demands of the industrial revolution 4.0 era, schools are required to integrate technology in managerial and pedagogical processes. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with principals and teachers, field observations, and documentation studies. Data analysis was carried out using miles and huberman. The results of the study show that: (1) Planning is carried out by integrating the vision of digitalization into the KOS and RKAS documents with the long-term target of developing multimedia spaces by 2026; (2) Organizing is carried out through the formation of a Media Team and the division of additional ICT tasks for teachers through SKBM to build a collaborative culture; (3) Implementation is shown through the use of Interactive Flat Panel (IFP) devices and digital platforms such as Quizizz and Canva to hone students' creativity and critical thinking; (4) Evaluation is carried out through monthly meetings and coaching clinics to overcome internet infrastructure barriers. The conclusion of the study emphasizes that the effectiveness of the implementation of digitalization policies in realizing students' 21st century skills is highly dependent on the consistent synchronization of POAC management stages. The success of digital transformation does not only rely on the availability of infrastructure, but also on strengthening systematic and sustainable school managerial governance.